Comparative Evaluation of Partial Substitution Mixture of Fine and Coarse Aggregates with Brick Kiln Powder and Recycled Coarse Aggregates in Rigid-pavement Based Cement-concrete Roads (International Journal of Innovative Research in Engineering & Management, 2022)
Fine and coarse aggregates are the most  common materials used in construction of cement concrete  roads, alternate substitutes to coarse and fine aggregates  like recycled aggregates and brick kiln powder have a  prospect to replace fine and coarse aggregates in road  constructions leading to effective cost-cutting, low  pollution and comparable material strength. This work  aimed to study the cost reduction of the cement concrete  road and pollution caused by brick kiln powder and  crushed aggregates and to see the strength properties of  rigid pavement upon partial replacement. We achieved the  study purpose by partially replacing the fine and coarse  aggregate with brick kiln powder and recycled coarse  aggregates. Subsequent analysis was performed by  measuring various properties of brick kiln powder,  admixture, fine aggregates, coarse aggregates, and  recycled aggregates. Compressive strength and flexural  strength tests were employed on the recycled coarse  aggregates and brick kiln powder concrete mix. The results  suggested the fact that a combination of brick kiln powder  and recycled coarse aggregate as a replacement against  conventional material is an effective material combination  nearly as equivalent to the conventional concrete at  replacements of 8% and 15%.
Keywords: Brick Kiln Powder; Recycled Aggregates; Compressive Strength; Fine Aggregate; Coarse Aggregate; Concrete Mix; Flexural Strength; Rigid Pavement; Crushed Aggregate